2019
DOI: 10.1371/journal.pntd.0007362
|View full text |Cite
|
Sign up to set email alerts
|

In-depth proteomic characterization of Schistosoma haematobium: Towards the development of new tools for elimination

Abstract: Background Schistosomiasis is a neglected disease affecting hundreds of millions worldwide. Of the three main species affecting humans, Schistosoma haematobium is the most common, and is the leading cause of urogenital schistosomiasis. S . haematobium infection can cause different urogenital clinical complications, particularly in the bladder, and furthermore, this parasite has been strongly linked with squamous cell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 92 publications
2
39
0
1
Order By: Relevance
“…Researchers found that glycoproteins such as IPSE (SmEP-25) [42], omega-1 [43], and kappa-5 [44] secreted by S. mansoni eggs and Sm29 [45] secreted by S. haematobium stimulate Th2 cytokine production in mice. For S. japonicum , egg secretory proteins (ESP) instead of IPSE, omega-1, and kappa-5 played a central role in driving the development of the immune response to the Th2 pattern because it was predicted to stimulate the production of IL-1, IL-3, IL-5, IL-4, and IL-13 [46].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that glycoproteins such as IPSE (SmEP-25) [42], omega-1 [43], and kappa-5 [44] secreted by S. mansoni eggs and Sm29 [45] secreted by S. haematobium stimulate Th2 cytokine production in mice. For S. japonicum , egg secretory proteins (ESP) instead of IPSE, omega-1, and kappa-5 played a central role in driving the development of the immune response to the Th2 pattern because it was predicted to stimulate the production of IL-1, IL-3, IL-5, IL-4, and IL-13 [46].…”
Section: Discussionmentioning
confidence: 99%
“…They may likely also be responsible for the dramatic changes in niche environments of the earlier stages of intra-mammalian schistosomula development. Braschi et al, 2006a,b;Van Hellemond et al, 2006;Sotillo et al, 2015Sotillo et al, , 2016Sotillo et al, , 2019 Enzymes (Esterases, carbonic anhydrase, Phosphodrolases, Thoredoxin peroxidase, Glyceraldehyde-3-phosphate dehydrogenase, protein disulfide isomerase, Glutathione S-transferase etc. )…”
Section: Potential Targets Functions Referencesmentioning
confidence: 99%
“…All other enzymes found on schistosomes tegument contribute toward the survival of the schistosomes. Braschi et al, 2006a;Van Hellemond et al, 2006;Mulvenna et al, 2010;Sotillo et al, 2015Sotillo et al, , 2016Sotillo et al, , 2019 McKenzie et al 2017, where the uptake of glucose was regulated in Schistosoma mansoni by Akt/Protein kinase B signaling. It was observed that Akt can be triggered by the host L-arginine, more so, insulin was shown to be effective in the layer of adult and schistosomula teguments.…”
Section: Potential Targets Functions Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main strategies the parasite’s employ to hijack the immune effector response is to release a suite of immunomodulatory excretory/secretory (ES) products. ES products comprise different proteins, glycans, lipids, and nucleic acids [14], and have been the focus of different studies aiming at understanding the molecular basis of host-parasite interactions and the subsequent use of this information to develop novel therapeutics and diagnostics [15-18]. Recently, it has been documented that the ES products from different helminths (including schistosomes) contain extracellular vesicles (EV)s [19-22].…”
Section: Introductionmentioning
confidence: 99%